Isolation And Evaluation Of cDNA Clones Specific To Polyclonal Antibody Against 12 kDa Excretory Secretory Antigen (ESA) Of Taxoplasma Gondii - Aziz, Farhanah Abdul (2012)
Toxoplasmosis is a zoonotic infection caused by Toxoplasma gondii. It is an obligate intracellular protozoan parasite distributed worldwide, with higher prevalence in the tropical countries. Although the risk of an overt disease in immunocompetent individuals is not high, severe manifestation may result when immunocompromised individuals and pregnant women are infected. It is very challenging yet crucial to establish whether acute infection has occurred in pregnant women as the fetus could be at risk of infection which can cause death or permanent organ damage.